CHARACTER EDUCATION IN SURAH AL-SAJDAH AND ITS IMPLEMENTATION IN AL-QUR'AN EDUCATIONAL INSTITUTIONS - Rokim, Syaeful; Wahidin, Unang; Triana, Rumba (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This article discusses educational essays contained in Surah As-Sajdah in the Qur'an. This Surah not only conveys the teachings of Islam but also contains educational values relevant to character development. The research also discusses its implementation in Qur'anic educational institutions, specifically a case study at Ma'had Huda Islami. This study uses a descriptive qualitative approach with the maudhui interpretation method, involving an in-depth examination of the verses of Surah As-Sajdah. Additionally, data were collected through observation, interviews, and document analysis. This article explores the educational messages that can guide Muslims in developing their Islamic understanding, shaping strong personalities, and strengthening moral and ethical foundations in daily life. The essay also examines how Surah As-Sajdah stimulates critical thinking, a spirit of learning, and cooperation in achieving goodness and justice. By integrating the educational values found in Surah As-Sajdah into the education system, it is hoped that a quality generation with a holistic vision of life can be formed.